Kompetensi Sosial-Emosional Guru Madrasah Ibtidaiyah dalam Membentuk Lingkungan Belajar yang Adaptif dan Inovatif - Sholehah, Riskawati (ELEMENTARY : Journal of Primary Education, 2025)
This study aims to analyze the role of socio-emotional competence of Madrasah Ibtidaiyah teachers in shaping an adaptive and innovative learning environment. Socio-emotional competence, which includes empathy, emotion regulation, communication skills and positive relationship building, is considered an important factor in creating a classroom environment that is responsive to students' needs and able to encourage learning innovation. This research approach uses a qualitative method with a case study design, involving Madrasah Ibtidaiyah teachers in several areas with diverse social backgrounds. Data were collected through in-depth interviews, participatory observation, and documentation analysis. The results show that teachers with high socio-emotional competence are able to create a learning environment that is more inclusive, collaborative and flexible to the changing needs of learners.